Fingerprints, Antioxidant Activity, and Anti-Tyrosinase of Fungus Comb Extract - Dewi, Trisni Untari; Diposani, Diva Putri; Rohaeti, Eti; Nandika, Dodi; Karlinasari, Lina; Arinana, Arinana; Santoso, Djoko; Witasari, Lucia Dhiantika; Rachmayanti, Yanti; Batubara, Irmanida (Jurnal Jamu Indonesia, 2023)
Fungus comb is a structure made by termite colony Macrotermitinae with lots of potential because it contains secondary metabolites such as steroids, terpenoids, and saponins and compounds containing antioxidant and anti-tyrosinase properties. This study aimed to determine fungus comb extracts' fingerprint pattern, antioxidant capacity, and anti-tyrosinase activity. Thin layer chromatography (TLC) was used to determine fingerprint patterns. The resulting TLC pattern was processed with ImageJ and converted into a densitogram. The fungus comb was extracted with n-hexane and ethyl acetate. TLC results showed that fungus comb extracts contain steroids and terpenoids and have antioxidant properties. The antioxidant capacity assay was carried out with 2,2-diphenyl-1-picrylhydrazyl reagent. N-hexane extract had an antioxidant capacity value of 9.07 mg ascorbic acid equivalent (AAE)/g extract, while ethyl acetate extract had 6.04 mg AAE/g extract. Anti-tyrosinase activity assay was carried out with L-tyrosine and L-3,4-dihydroxyphenylalanine (L-DOPA) as substrates. N-hexane extract had a better anti-tyrosinase activity with IC50 of 1804 µg/mL for L-tyrosine and 6784 µg/mL for L-DOPA.